RAGAM POLA TABUHAN KESENIAN ZIKIR SALAI DI DESA TRIMANDAYAN KECAMATAN TELUK KERAMAT KABUPATEN SAMBAS - Welli Aprian; Imam Ghozali; Asfar Muniir (Universitas Tanjungpura, 2021)
AbstractThe background of this research is to study the technique of playing a membrane musical instrument and the variation of the beat patterns of Zikir Salai in Trimandayan Village, Teluk Keramat District, Sambas Regency. The purpose of this study was to describe the technique of playing membrane musical instruments and to concern the various rhythmic patterns of Zikir Salai in Trimandayan Village. The method used was descriptive analytic with a musicological approach. The data in this research were in the form of rebana and gedomba 'musical instrument playing techniques, and the beat pattern of the Zikir Salai in Trimandayan Village. The participants in this study were the artist figures who knew about this art. Data collection was done by observing, interviewing, and documenting, checking the validity of the data by extending observations and triangulating sources. The data analysis technique used was the analisys content technique of Moleong's (1991) model. Based on the data analysis Rebana and Gedomba’ had two kinds of sound “dung” and “cang”, there were five beat patterns one basict beat, two basic beat, tandak beat, keroncong beat, and dangdut beat, there are also rhythmic development of every basic beats and also techniques expansion and tone color “dung” on dangdut beat. Finally researcher hopes this research can stimulate the interest to learn traditional art especially Zikir Salai in Trimandayan Vilage Teluk Keramat District on Sambas Regency.Keywords: Pattern of beat, Traditional Art, Zikir Salai.